An engineered solution to the maladministration of spinal injections. Issue 6 (2nd December 2009) - Lawton, R; Gardner, P; Green, B; Davey, C; Chamberlain, P; Phillips, P; Hughes, G
Abstract : Background: An overview is provided of the progress made in a Department of Health (DH) initiative to implement an engineered solution to the maladministration of spinal injections. In an effort to eliminate the possibility of misconnection errors at the spinal route, the DH is investigating the potential for dedicated spinal equipment that will be incompatible with standard Luer syringes, needles and associated devices. Method: Background information on the problem of misconnection errors is provided and a systematic approach to their eradication is detailed. Research to date has entailed extensive bench-testing of prototype non-Luer connectors, a prospective hazard analysis of spinal procedures in haematology and anaesthesia and usability evaluation of prototype non-Luer devices in simulated environments. Results: The prospective hazard analysis identified two potential risks which will need to be managed as part of a successful implementation programme. Conclusion: Usability testing of two prototype connection systems concluded that one design was inadequate, as the non-Luer element was provided as a separable adapter. The second connection system was modified following the first round of testing, and achieved improved satisfaction ratings from clinicians in round two. This system was selected to proceed to a pre-implementation evaluation and the research team are currently evaluating its acceptability in clinical use.